2021
DOI: 10.3390/ijms22115681
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinamide N-Methyltransferase in Acquisition of Stem Cell Properties and Therapy Resistance in Cancer

Abstract: The activity of nicotinamide N-methyltransferase (NNMT) is tightly linked to the maintenance of the nicotinamide adenine dinucleotide (NAD+) level. This enzyme catalyzes methylation of nicotinamide (NAM) into methyl nicotinamide (MNAM), which is either excreted or further metabolized to N1-methyl-2-pyridone-5-carboxamide (2-PY) and H2O2. Enzymatic activity of NNMT is important for the prevention of NAM-mediated inhibition of NAD+-consuming enzymes poly–adenosine -diphosphate (ADP), ribose polymerases (PARPs), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 131 publications
(159 reference statements)
0
16
0
Order By: Relevance
“…NNMT has been shown to modulate the epigenetic environment in the differentiation process of stem cells [54,55] and is elevated in cancer stem cells compared to non-tumour cells [55][56][57]. Increased amounts of NNMT alter the methylation status of the genome by reducing available SAM, favouring a pattern of gene expression which promotes the dedifferentiated state and thus drives the evolution of the cell towards a cancer phenotype [56,[58][59][60]. Hence, it is likely that NNMT holds a central role in the promotion of the cancer phenotype.…”
Section: Nnmt Promotes the Cancer Phenotypementioning
confidence: 99%
See 1 more Smart Citation
“…NNMT has been shown to modulate the epigenetic environment in the differentiation process of stem cells [54,55] and is elevated in cancer stem cells compared to non-tumour cells [55][56][57]. Increased amounts of NNMT alter the methylation status of the genome by reducing available SAM, favouring a pattern of gene expression which promotes the dedifferentiated state and thus drives the evolution of the cell towards a cancer phenotype [56,[58][59][60]. Hence, it is likely that NNMT holds a central role in the promotion of the cancer phenotype.…”
Section: Nnmt Promotes the Cancer Phenotypementioning
confidence: 99%
“…For example, it is possible that the pro-tumour effects of MNA arises from its binding and consequent stabilisation and activation of sirtuins [70][71][72][73], the consequences of which for the tumour cell include pro-oncogenic changes in epigenetic regulation and protein acetylation [22,23] along with enhancement of chemoresistance [70]. Anti-tumour effects of MNA may at the same time arise from its inhibition of NNMT activity [1,31,63,155] and its subsequent effects upon nicotinamide levels, NAD+ synthesis and cellular SAM availability, the consequences of which include decreased activity of NAD+-dependent pro-oncogenic enzymes such as PARP-1 [141][142][143][144] and reversal of pro-oncogenic changes in epigenetic regulation [56,[58][59][60], as well as increased production of PGI 2 . What is clear is that further research is required to fully elucidate the role of MNA in tumour survival and progression.…”
Section: Synthesis Of 1-methylnicotinamidementioning
confidence: 99%
“…In addition to this, recent studies showed that the enrichment of tumor cell lines with CSCs was significantly associated with the enhanced expression of NNMT [76,78]. Acquisition of stem-like phenotype by cancer cells was demonstrated to have detrimental effects in terms of tumor aggressiveness and its resistance to therapy, thus leading to the relapse of neoplasm and metastatic spread [116]. In the light of these considerations and based on data reported in this review, it is conceivable to hypothesize NNMT involvement in those molecular processes and cellular events featuring poor clinical outcomes of urological malignancies.…”
Section: Discussionmentioning
confidence: 98%
“…In 1951, Cantoni first partially purified nicotinamide N-methyltransferase (NNMT) from rat liver [57] and subsequently discovered the structure of the cofactor SAM, which is an active methyl donor [58]. The enzymatic activity of NNMT is important for preventing the nicotinamide (NAM)-mediated inhibition of NAD+-consuming enzymes (such as polyadenosine-diphosphate, ribose polymerases, and sirtuins) [59]. NNMT activity alteration has been reported in oral, stomach, colon, rectum, liver, pancreas, breast, bladder, prostate, ovary, and lung tumors as well as in glioma, lymphoma, and insulinoma [60][61][62].…”
Section: Nicotinamide Adenine Dinucleotide (Nad+) Salvage Pathway In Cancermentioning
confidence: 99%
“…The activity of NNMT is tightly linked to the maintenance of the NAD+ level in cells [59]. A recent study on TME via a combination of metabolomics and single-cell RNA sequencing analysis indicated that cells within ascites and ovarian cancer showed a notable enrichment in MNAM in tumor-infiltrating T cells.…”
Section: Nicotinamide Adenine Dinucleotide (Nad+) Salvage Pathway In Cancermentioning
confidence: 99%